2018
DOI: 10.1080/15332640.2018.1456387
|View full text |Cite
|
Sign up to set email alerts
|

Risks of opioid abuse among uninsured primary care patients utilizing a free clinic

Abstract: The annual number of opioid prescriptions for pain relief has been increasing in the United States. This increase has raised concerns about prescription opioid abuse and overdose. The purpose of this study was to examine opioid risks (risk factors that increase the chance of opioid abuse) among uninsured primary care patients utilizing a free clinic. Data were collected using a self-administered paper survey in the waiting room of the free clinic from May to July 2017 (N = 506). Higher levels of somatic sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These risk factors are inextricably linked to personal and environmental factors and systems that hinder rather than support individuals [6]. For instance, among individuals receiving healthcare services at a free clinic, prescription opioid misuse was more likely among patients who were employed and less likely among those with post-high school education [7]. Uninsured individuals were significantly more likely than insured individuals to be high-risk drug users [8].…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors are inextricably linked to personal and environmental factors and systems that hinder rather than support individuals [6]. For instance, among individuals receiving healthcare services at a free clinic, prescription opioid misuse was more likely among patients who were employed and less likely among those with post-high school education [7]. Uninsured individuals were significantly more likely than insured individuals to be high-risk drug users [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed higher adverse event rates in zip codes with only English-speaking individuals, consistent with increased suicide rates in rural English-speaking areas( 146 ). Concerns over opioid abuse and overdose have also risen, with U.S.-born English speakers displaying higher opioid risk levels compared to non-U.S. born language speakers( 147 ). Language, employment, and education status contribute to increased opioid risks.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using IBM SPSS ver 22. The analyses were primarily based on the comparison of the following 3 groups: US born English speakers, non-US born English speakers, and Spanish speakers because previous studies at the free clinic suggest the 3 groups reported different levels of substance use and opioid risks (6). The 3 groups were compared by Pearson w 2 tests for categorical variables and analysis of variance (ANOVA) tests for continuous variables.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on opioid risks among uninsured individuals using a free clinic indicated several gaps in opioid-related research (6). First, opioid abuse among Hispanic free clinic patients needs to be further examined because there is little research regarding this population.…”
Section: Introductionmentioning
confidence: 99%